Alkali activated slag concrete incorporating recycled aggregate concrete: Long term performance and sustainability aspect. (15th February 2021) - Nanayakkara, Ominda; Gunasekara, Chamila; Sandanayake, Malindu; Law, David W.; Nguyen, Kate; Xia, Jun; Setunge, Sujeeva
Highlights: AAS–RA concrete attained 90% compressive strength produced by AAS–RA concrete. AAS–RA concrete showed lower chloride permeability and sorptivity in long term. Extending water curing upto 28 days reduces drying shrinkage of AAS-RA concrete. Porous external surface is attributed to initial water absorption in AAS-RA concrete. AAS-RA concrete displayed 52% carbon emission reduction than PC concrete. Abstract: Adaption of reclaimed resources within the construction industry, in order to move towards environmental sustainability and a carbon neutral society is essential. To address this issue this study focused on the investigation of the long term performance, carbon emissions and coast savings of Alkali-activated slag (AAS) concrete incorporating recycled coarse aggregate (AAS-RA) up to one year of age. The performance and sustainability aspect of AAS-RA concrete was then compared with AAS concrete incorporated with natural quarry aggregate (AAS-NA) and PC concrete, respectively. Both AAS concretes achieved similar compressive strength of approx. 40 MPa and tensile strength of approx. 3.3 MPa after one year. Hence, full replacement of quarried coarse aggregate using recycled aggregate in AAS concrete did not display any evidence of an adverse impact to the strength characteristics. However, the 7-day and 28-day water cured AAS concretes demonstrated 32% and 16% higher drying shrinkage at one year in excess of the maximum permissible limit specified in AS3600. Both AAS concretes displayed high water absorption but low chloride permeability and sorptivity. A highly porous external surface layer interconnected with numerous capillaries and microcracks is hypothesised to be the reason for the high water absorption. Gel formation densified the microstructure and filled the capillaries in the bulk matrix, which in turn resulted in the lower permeability and secondary sorptivity. The AAS-NA and AAS-RA concretes displayed 43.5% and 52% carbon emission reduction compared to an equivalent strength of PC concrete having similar binder content.